Anticancer effects of traditional Chinese herbs with phlegm-eliminating properties – An overview. (22nd August 2015) - Xiu, Li-Juan; Sun, Da-Zhi; Jiao, Jian-Peng; Yan, Bing; Qin, Zhi-Feng; Liu, Xuan; Wei, Pin-Kang; Yue, Xiao-Qiang
Abstract: Ethonopharmacological relevance: Cancer is considered to be the second leading cause of human death. It is unsatisfactory that in the past decades, the treatment for cancer has not progressed as fast as it was expected, as only 50% of newly diagnosed patients could be cured even today. The development of cancer is a multifactorial process, involving tumor cells themselves, the interactions between tumor cells and their microenvironments, as well as the interactions between tumor cells and the host׳s immunity. Focusing on any single goal may bring limited benefits. Aim and methods of the study: Phlegm-eliminating herbs, which can reduce phlegm and eliminate pathological metabolites, are commonly used to treat cancer in China. However, the underlying molecular targets and efficacy of herbal medicines in cancer treatment still remain unclear. In this study, we reviewed the potential anticancer mechanisms of some phlegm-eliminating herbs and their active ingredients from the articles through such scientific databases as MEDLINE, PubMed, and Google Scholar. Results: We found that the anticancer mechanisms of phlegm-eliminating herbs and ingredients include inducing apoptosis, anti-proliferation, preventing tumor invasion and metastasis, and reducing resistance to chemotherapy. In addition, some phlegm-eliminating herbs and their ingredients have anti-inflammatory and anti-metabolic syndrome effects. Conclusions: We suggest that the phlegm-eliminating herbs and ingredients are potential candidates for anticancer treatment and cancer prevention by playing a comprehensive role. Graphical abstract: